Air-breathing membraneless laminar flow-based fuel cell with flow-through anode - Shaegh, Seyed Ali Mousavi (2012)
This paper describes a detailed characterization of laminar flow-based fuel cell (LFFC) with air-breathing cathode for performance (fuel utilization and power density). The effect of flow-over and flow-through anode architectures, as well as operating conditions such as different fuel flow rates and concentrations on the performance of LFFCs was investigated. Formic acid with concentrations of 0.5 M and 1 M in a 0.5 M sulfuric acid solution as supporting electrolyte were exploited with varying flow rates of 20, 50, 100 and 200 μl/min. Because of the improved mass transport to catalytic active sites, the flow-through anode showed improved maximum power density and fuel utilization per single pass compared to flow-over planar anode. Running on 200 μl/min of 1 M formic acid, maximum power densities of 26.5 mW/cm2 and 19.4 mW/cm2 were obtained for the cells with flow-through and flow-over anodes, respectively. In addition, chronoamperometry experiment at flow rate of 100 μl/min with fuel concentrations of 0.5 M and 1 M revealed average current densities of 34.2 mA/cm2 and 52.3 mA/cm2 with average fuel utilization of 16.3% and 21.4% respectively for flow-through design. The flow-over design had the corresponding values of 25.1 mA/cm2 and 35.5 mA/cm2 with fuel utilization of 11.1% and 15.7% for the same fuel concentrations and flow rate.